2010
DOI: 10.1002/ajh.21726
|View full text |Cite
|
Sign up to set email alerts
|

XPC genetic polymorphisms correlate with the response to imatinib treatment in patients with chronic phase chronic myeloid leukemia

Abstract: Chronic myeloid leukemia (CML) is driven by the BCR-ABL protein, which promotes the proliferation and viability of the leukemic cells. Moreover, BCR-ABL induces genomic instability that can contribute to the emergence of resistant clones to the ABL kinase inhibitors. It is currently unknown whether the inherited individual capability to repair DNA damage could affect the treatment results. To address this, a comprehensive analysis of single nucleotide polimorfisms (SNPs) on the nucleotide excision repair (NER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…101 In addition, DNA ligase I, a ligase involved in nucleotide excision repair and base excision repair, has recently been implicated in backup NHEJ, where it was associated with promoting chromosomal translocations. 102 Moreover, singlenucleotide polymorphisms in the DNA ligase I gene were found in patients with chronic myeloid leukaemia 103 and some mutations are connected to increased risk of lung cancer. 104 So far, no human cancer has been associated with XLF mutations.…”
Section: Mechanisms Of Cancer Developmentmentioning
confidence: 99%
“…101 In addition, DNA ligase I, a ligase involved in nucleotide excision repair and base excision repair, has recently been implicated in backup NHEJ, where it was associated with promoting chromosomal translocations. 102 Moreover, singlenucleotide polymorphisms in the DNA ligase I gene were found in patients with chronic myeloid leukaemia 103 and some mutations are connected to increased risk of lung cancer. 104 So far, no human cancer has been associated with XLF mutations.…”
Section: Mechanisms Of Cancer Developmentmentioning
confidence: 99%
“…In contrast, the mutant TT homozygotes or CT heterozygotes in XPC499 had an increased likelihood of nonresponders compared to the wild-type CC homozygotes. No significant difference was observed for other SNPs (Guillem et al, 2010).…”
Section: Advanced Pharmacogenomics Using Dna Sequencing Technologies mentioning
confidence: 64%
“…Several reports recently demonstrated the association between SNPs and the responses to gene therapy (Table 3). The response to imatinib treatment in patients with chronic myeloid leukemia (CML), as a good example for this approach, has been performed (Guillem et al, 2010). Imatinib, which is a remarkably effective drug for CML that results from the clonal expansion of pluripotent hematopoietic stem cells containing the BCR-ABL fusion gene, permits long-term disease control in about three fourths of patients, but some patient do not respond to the treatment (Druker et al, 2006).…”
Section: Advanced Pharmacogenomics Using Dna Sequencing Technologies mentioning
confidence: 99%
“…It has been shown that the assessment of DNA repair characteristics can be very informative in the choice and prediction of the outcome of therapy, even though further studies with a larger number of patients are often required for confirmation of results. Polymorphisms in the NER genes XPG and XPC, for instance, are associated with the differential response of chronic myeloid leukemia patients to treatment with imatinib (170). The A23G polymorphism of the NER gene XPA is associated with increased response of non-small cell lung cancer patients to platinum-based chemotherapy (171).…”
Section: Dna Repair and Cancer Chemotherapymentioning
confidence: 99%